Implementasi Robot Cerdas Pemadam Api dengan Multi Independent Steering - Rodi Hartono; Gyan Aditiya Firdaus (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2018)
Abstract - Robot technology appears to ease human work. With devices such as fire fighting robots, rescue robots, surveillance robots, and robots whose functions differ according to field needs. In this paper, we have the idea of implementing an intelligent fire extinguisher robot with multi-independent steering that can be directed to the location of the fire to find the source of hotspots. With multi-independent steering, the wheels on the robot can navigate and move swiftly on each wheel that moves in all directions. In this paper we simulate by searching for candles as a source of hotspots. When this robot finds a source of fire, this robot will turn off the candle or source of the fire automatically. This robot contains the following functional components: ultrasonic to find out the surrounding field, a light sensor to look for sources of hotspots or light sources, and a fan to turn off the candle or the point of fire. In terms of design, although the designs of robots are minimalist and small, they provide protection at high temperatures, excellent waterproof when exposed to water spray, and a high impact resistance. As well as creating an automatic robot that aims to find a way automatically to find the presence of hotspots on the fire field without being controlled. This study aims to provide an automatic fire extinguisher system that can help and lighten the fire extinguishing profession which has a high level of risk in its operation. The results of this study will be able to create an intelligent robot that can minimize the risk of the work of a fire extinguisher profession with a multi-independent steering method. By using this method the steering system where each wheel can move freely. With this steering system the robot can move freely in all directions and is a type of holomonic motionKeyword : Fire extinguisher robot, robotic system, portable evacuation guide, multi-independent steering